Treasures from Korea arts and culture of the Joseon Dynasty, 1392-1910 - Woo, Hyunsoo; Woo, Hyunsoo; Kim, Hongkyung; Cho, Insoo; Song, Unsok; Lee, Rose; Kwon, So-hyun; Kim, Woollim; Moon, Dongsoo (Yale University Press, 2014)
The Joseon dynasty left a substantial legacy for modern Korea, influencing contemporary etiquette, cultural norms, and societal attitudes. This book intends to survey the artistic production of the world's longest-ruling Confucian dynasty, which reigned on the Korean peninsula from 1392 to 1910